Problems and solutions in teaching English pronunciation to primary school learners (Texas Journal of Philology, Culture and History, 2025)
This article explores the key challenges and practical solutions in teaching English pronunciation to primary school learners. Pronunciation plays a vital role in the early stages of language acquisition, directly impacting learners' ability to understand and use the language effectively. Based on a study conducted with teachers and students at School No. 66 in Chust, Uzbekistan, the article identifies common pronunciation issues such as phonetic interference from the mother tongue, mispronunciation of unfamiliar English sounds, incorrect stress and intonation, and limited phonemic awareness. Specific difficulties include pronouncing sounds like [θ], [ð], and [w], as well as understanding non-phonetic English spellings. To address these challenges, the study suggests integrating methods such as phonics-based instruction, use of minimal pairs, mirror exercises, tongue twisters, and interactive digital tools like Lingokids and ELSA Speak. Additionally, poems, dialogues, and consistent teacher modeling are emphasized as effective strategies to reinforce correct pronunciation. The findings underscore the importance of early and continuous pronunciation instruction using auditory, visual, and kinesthetic techniques to help young learners build confidence and fluency in English